Retrograde BMP signaling activates neuronal gene expression through widespread deployment of a conserved BMP-responsive cis-regulatory activation element. Issue 2 (22nd November 2018) - Vuilleumier, Robin; Lian, Tianshun; Flibotte, Stephane; Khan, Zaynah N; Fuchs, Alisa; Pyrowolakis, George; Allan, Douglas W
Abstract: Retrograde Bone Morphogenetic Protein (BMP) signaling in neurons is essential for the differentiation and synaptic function of many neuronal subtypes. BMP signaling regulates these processes via Smad transcription factor activity, yet the scope and nature of Smad-dependent gene regulation in neurons are mostly unknown. Here, we applied a computational approach to predict Smad-binding cis -regulatory BMP-Activating Element s ( BMP-AE s) in Drosophila, followed by transgenic in vivo reporter analysis to test their neuronal subtype enhancer activity in the larval central nervous system (CNS). We identified 34 BMP-AE -containing genomic fragments that are responsive to BMP signaling in neurons, and showed that the embedded BMP-AEs are required for this activity. RNA-seq analysis identified BMP-responsive genes in the CNS and revealed that BMP-AE s selectively enrich near BMP-activated genes. These data suggest that functional BMP-AE s control nearby BMP-activated genes, which we validated experimentally. Finally, we demonstrated that the BMP-AE motif mediates a conserved Smad-responsive function in the Drosophila and vertebrate CNS. Our results provide evidence that BMP signaling controls neuronal function by directly coordinating the expression of a battery of genes through widespread deployment of a conserved Smad-responsive cis -regulatory motif.